LEWIS PYENSON, SUSAN SHEETS-PYENSON, Servants of Nature. A History of Scientifi c Institutions, Enterprises and Sensibilities, New York-London 2000, W. W. Norton & Company, 496 s., ISBN 0-393-31736-6 - Krausová, Jiřina (Dějiny – teorie – kritika, 2014)
Book review